A Production systems study on KYZ Industrial Corp. - Casabar, Mayumi; de Asis, Cristina; Dimayuga, Bernadette; Santos, Almira (College of Engineering, 1994)
This production systems study focuses on a division of a packaging firm which manufactures sanitary cans. Presently, according to the plant manager, their factory is faced with shortages in inventory space. To solve this problem of accumulation of unwanted inventory, the group looked into the forecasting technique being used by the company, compared this with the actual demand, and sought out other forecasting methods which are applicable. It was found out that the company was over-estimating their demand based on "gut-feel" forecasting. A regression analysis was performed to make forecasts. The forecasts were found to approximate the actual demand better than the plant manager's own method. Demand for the five sizes was forecasted for 1994 by the group using regression analysis. Results were consulted with the plant manager ti verify its validity based on the industry trend. According to the plant manager, a linear equation may have been applicable to the data in 1992, but using such an equation for the succeeding years may yield highly improbable demands. Industry growth does not grow as rapidly and continuously. If such an equation was followed, the factory will be under-capacity in no time. The plant manager suggested that a 10% yearly increase in demand will be more realistic. Thus, in deference to experience and wisdom, the group decided to follow this suggestion in determining the demand for 1994, and succeeding years to determine approximately when the full capacities for the different machines will be reached. The inventory was cut down by applying a 1,5 month stock-level policy. Production plan covers a few years starting from 1994 to determine the point in time when the 1.5 policy may not be feasible anymore as constrained by the maximum allowable capacity of the machines. At the event that infeasibility is reached, lowering the stock level while maximizing capacity, is suggested. The plant layout was also evaluated, and a suggestion was made to move the end lines closer to the body lines to reduce travel time. Finally, to help the company establish the sound manufacturing practices in their plant, the present system was analyzed and the concept of 5S was introduced.